What Is the Role of AI in Traumatic Brain Injury Assessment? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2016)
Traumatic brain injury (TBI) represents a significant global health challenge, contributing to high rates of mortality and long-term disability. The assessme...
Keywords: AI in Neurology; Traumatic; Brain; Injury; Artificial Intelligence; Machine Learning; Deep Learning